Dynamic thiol / disulfide homeostasis in metabolically healthy obese adolescents - Yuce, Ozge; Erel, Ozcan (Annals of Medical Research, 2021)
Aim: This study aim to discuss the possible role of oxidant-antioxidant balance in providing metabolic health in obese adolescents by determining the oxidant-antioxidant status. Material and Methods: 98 metabolically healthy obese and 75 normal-weight adolescents participated in the study. Obese individuals were grouped according to the severity of obesity. Biochemical parameters including thiol/ disulfide homeostasis were analyzed. Serum native thiol (SH), total thiol (SH+SS) and disulfide (SS) concentrations were determined using a novel automated measurement method. Disulfide to native thiol ratio (SS/SH), disulfide to total thiol ratio(SS/(SH+SS)), and native thiol to total thiol ratio (SH/(SH + SS)) were calculated and were presented as percentage. Results: Native and total thiol levels-as an antioxidative parameter-was significantly higher in obese adolescents compared to healthy-weight adolescents (p0.001). Native thiol/total thiol ratio was slightly higher in the obese group, but not statistically significant (p=0.4). Disulfide levels, disulfide/native thiol and disulfide/total thiol ratios were not different between the groups. We found that the levels of the antioxidant parameters, native thiol, and total thiol increased significantly along with the severity of the obesity, while other parameters remained comparable. We also found a significant increase in antioxidant parameters correlated with the severity of obesity (p0.001). Conclusion: This study concluded that the increased antioxidant status and activity in obese adolescents may be related to the metabolic health.
Keywords: Thiol/Disulfide; obesity; adolescent; oxidative stress